„Ложка страху в діжці мотороші”, або кілька слів про найновішу українську антологію жахів - Горнятко-Шумилович, Анна (Poznańskie Studia Slawistyczne, 2019)
The release of the newest anthology of macabre short stories “Вбивство на вулиці...” (2019) affirmed the superb state of homebred horror literature. The aim of this paper is to analyze and evaluate the seventeen stories that form the aforementioned anthology. Analysis of the anthology has proven that despite a few creative shortcomings of young litterateurs, the “Вбивство на вулиці...” anthology maintains a high level of quality and deserves to be called a bestseller.